Cardiorespiratory fitness, body mass index, cardiovascular disease, and mortality in young men: A cohort study - Gorny, Alexander Wilhelm; Yap, Jonathan; Neo, Jia Wei; Chow, Wei En; Yeo, Khung Keong; Tan, Chuen Seng; Müller-Riemenschneider, Falk (Frontiers in Public Health, 2023)
Objective: We examined the association between cardiorespiratory fitness (CRF), body-mass index (BMI) and incidence of major acute cardiovascular events (MACE) and all-cause mortality (ACM). Methods: We conducted a retrospective cohort study involving 212,631 healthy young men ages 16 to 25 years who had undergone medical examination and fitness testing (2.4km run) from 1995 to 2015. Information on outcomes of major acute cardiovascular events (MACE) and all-cause mortality (ACM) were obtained from national registries. Results: During 2,043,278 person-years of follow-up 371 first MACE and 243 ACM events were recorded. Comparing against the first run-time quintile, adjusted hazard ratios (HR) for MACE in the second to fifth quintiles were 1.26 (95% CI 0.84-1.91), 1.60 (95% CI 1.09-2.35), 1.60 (95% CI 1.10-2.33) and 1.58 (95% CI 1.09-2.30), respectively. Comparing against the ‘acceptable risk’ BMI category, adjusted HRs for MACE in the ‘underweight’, ‘increased risk’ and ‘high risk’ categories were 0.97 (95% CI 0.69-1.37), 1.71 (95% CI 1.33-2.21) and 3.51 (95% CI 2.61-4.72). Adjusted HRs for ACM were increased in participants from the fifth run-time quintile, 'underweight' and ‘high risk’ BMI categories. Combined associations of CRF and BMI with MACE showed elevated hazard in the ‘BMI≥23-fit’ category which was more pronounced in the ‘BMI≥23-unfit’ category. Hazards for ACM were elevated across ‘BMI<23-unfit’, ‘BMI≥23-fit’ and ‘BMI≥23-unfit’ categories. Conclusion: Lower CRF and elevated BMI were associated with increased hazard of MACE and ACM. Higher CRF did not fully compensate for elevated BMI in combined models. CRF and BMI remain important targets for public health intervention in young men.